Seizure, Deafness, and Renal Failure: A Case of Barakat Syndrome - Nasrollah Maleki; Bahman Bashardoust; Manouchehr Iranparvar Alamdari; Zahra Tavosi (Case Reports in Nephrology)
Barakat syndrome (also known as HDR syndrome) is an autosomal dominant disorder characterized by hypoparathyroidism, sensorineural deafness, and renal disease caused by mutation of the GATA3 gene located at chromosome 10p15. The exact prevalence of this disorder is not known but is very rare, with only about a dozen cases reported in the literature. Here, we report a case of 58-year-old man from Ardabil who presented with seizure due to hypocalcemia. Further history revealed bilateral deafness. Audiogram confirmed sensorineural hearing loss of both sides. His laboratory data were consistent with hypoparathyroidism and renal failure. He was diagnosed to have Barakat syndrome based on his clinical and laboratory data. In conclusion, we need to be aware of rare inherited conditions in a patient with abnormal physical and laboratory findings even though their initial presentation was seizure and hypocalcemia.